Modele zarządzania jakością - Bobik, Dorota (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Due to competition which is tougher and tougher there are many companies searching for more and more up to date concepts leading to boosting business. A lot of them want to enhance their performance, choose and implement modern quality management models. All these models are based on PDCA - a well-known concept called plan-do-check-and act and picture a company as a unity in terms of answering customer's needs. Whether it is focusing on customer (TQM, EFQM model), customer's perspective (BSC), process approach (ISO 9001:2000), or focusing on features that are critical for customer (Six Sigma) - a satisfied customer is the centre point. Growing interest in new approaches, such as universal quality management models, has been prompted by the need to seek more effective ways of management in new market environment no matter what type of organization and sector it works in. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 163-176